2018
DOI: 10.3151/jact.16.382
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Mechanical Properties of SBR-Modified Mortar with Fly Ash for Patch Repair Material

Abstract: This work determines the replacement ratio of fly ash of 25% in SBR-modified cement mortars based on the past research, including SBR emulsion (SBR-E) and SBR powder (SBR-P). In addition to the Japanese guidelines for the repair material, the past researches related to polymer-modified cement mortars are also used to determine an appropriate mix proportion of the patch repair material for deteriorated RC building structures. According to the experimental results in this work, it can be observed that increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Wang et al found that with styreneacrylate (SAE) powder added, the bond strength of ordinary mortar increased from 0.97 to 1.3 MPa to 3.12-2.87 MPa (WANG and ZHANG, 2015). Kao et al found that adding styrene-butadiene rubber (SBR) powder to mortar resulted in a tensile strength of 3.35 MPa for repair specimens (KAO et al, 2018). When SBR polymer was added to mortar, the shrinkage measured after 1 year was 1/3 less than that of ordinary silicate cement mortar, which can significantly improve the bond strength (MOMAYEZ et al, 2005a).…”
Section: Mortar Of Different Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al found that with styreneacrylate (SAE) powder added, the bond strength of ordinary mortar increased from 0.97 to 1.3 MPa to 3.12-2.87 MPa (WANG and ZHANG, 2015). Kao et al found that adding styrene-butadiene rubber (SBR) powder to mortar resulted in a tensile strength of 3.35 MPa for repair specimens (KAO et al, 2018). When SBR polymer was added to mortar, the shrinkage measured after 1 year was 1/3 less than that of ordinary silicate cement mortar, which can significantly improve the bond strength (MOMAYEZ et al, 2005a).…”
Section: Mortar Of Different Componentsmentioning
confidence: 99%
“…The researchers found that modified mortar polymer film prepared by SAE powder had high film density and good toughness. It was more suitable as a repair material than SAE emulsion (WANG and ZHANG, 2015;KAO et al, 2018). However, in underwater conditions, the poor performance of polymer mortar affects bond strength (QIAN et al, 2016).…”
Section: Mortar Of Different Componentsmentioning
confidence: 99%
“…Tro bay cũng đã được nghiên cứu để thay thế hoàn toàn xi măng (100% FA/OPC) làm chất kết dính, kết hợp với các chất hoạt hóa phù hợp để tạo ra loại bê tông geo-polymer có cường độ mẫu trụ trung bình đạt tới 50 MPa và được nghiên cứu áp dụng cho kết cấu chịu uốn [9]. Tuy nhiên, chưa có nhiều nghiên cứu ứng dụng của bê tông có tro bay thay thế một phần xi măng làm chất kết dính vào cấu kiện BTCT chịu nén uốn [10][11][12][13][14][15][16][17].…”
Section: Giới Thiệuunclassified
“…In the current global trend of sustainable construction, the utilization of industrial by-product such as fly ash (FA) for concrete to reduce the production of ordinary Portland cement (OPC) has attracted researchers' attentions for a few decades. Initially, FA was mostly utilized as an additive with a limit dose for the concrete admixture to improve workability of fresh concrete [13][14][15][16][17][18][19][20]. The actual FA amount used varies widely depending on the application, mechanical and chemical properties of FA, specification limits, as well as on the geographic location and climate.…”
Section: Introductionmentioning
confidence: 99%